Laparoscopic Partial Nephrectomy: Is It Worth Still Performing the Retroperitoneal Route? - Idir Ouzaid; Evanguelos Xylinas; Géraldine Pignot; Arnaud Tardieu; Andras Hoznek; Clément-Claude Abbou; Alexandre de la Taille; Laurent Salomon (Advances in Urology)
Objective. The objective of this study was to compare perioperative, oncologic, and functional outcomes of TLPN (transperitoneal laparoscopic partial nephrectomy) versus RLPN (retroperitoneal). Patients and Methods. From 1997 to 2009, a retrospective study of 153 consecutive patients who underwent TLPN or RLPN for suspicious renal masses was performed. Complications, functional and oncological outcomes were compared between the 2 groups. Results. With a mean followup of 39 and 32 months, respectively, 66 and 87 patients had TLPN and RLPN, respectively. Tumor location was more often posterior in the RLPN and more often anterior in the TLPN. Mean operative time and mean hospital stay were longer in the TLPN group with 190±85 min versus 154±47 (𝑃=0.001) and 9.2±6.4 days versus 6.2±4.5 days (𝑃<0.05), respectively. Transfusion and urinary fistulas rates were similar in the 2 groups. After 3-year followup, chronic kidney failure occurred in 6 and and 4% (𝑃=0.67) in after TLPN and RLPN, respectively. After 3-year followup, recurrence free survival was 96.7% and 96.6% (𝑃=0.91) in the TLPN and RLPN groups, respectively. Conclusion. Our study confirmed that TLPN had longer operative time and hospital stay than RLPN. The complication rates were similar. Furthermore, mid-term oncological and functional outcomes were similar.